Cellphone addiction during the Covid-19 outbreak: How online social anxiety and cyber danger belief mediate the influence of personality. (August 2021) - Zhan, Zehui; Wei, Qing; Hong, Jon-Chao
Abstract: The highly contagious Covid-19 virus is spreading around the world, and quarantining at home has become one of the main preventative behaviors, but it has also led to news blackouts, affecting people's normal life and interactions. In order to determine a predictor of cellphone addiction (CPA), the present study, based on the Risk of Information Seeking and Processing (RISP) model, investigated the relationship between personality (Neuroticism and Extraversion) and CPA during the epidemic, mediated by online social anxiety (OSA) and cyber danger belief (CDB). A total of 683 questionnaires were collected through snowball sampling and analyzed by Mplus. Results indicated that neurotic and extroverted individuals developed CPA through different mediating factors. Neuroticism affected CPA through OSA while Extraversion affected CPA through CDB. These findings highlight the importance of different mechanisms of individuals with different personalities. Corresponding cognitive treatments on the perception of social anxiety and cyber danger are recommended on neurotic and extroverted individuals, respectively, in order to reduce their degree of CPA. Highlights: Neurotic people and Extroversive people develop cellphone addiction through different mediating factors and mechanisms. Neuroticism affects cellphone addiction through online social anxiety. Extraversion affects cellphone addiction through cyber danger belief. The good fit of the current model supports the feasibility of the RISP theory at the micro level of mobile phone addiction. COVID-19 increased individuals' reliance on smartphones while their personalities become more tendentious.